Harmonic Response Analysis of Tank Design Effect on Ultrasonic Cleaning Process - Suchada Phophayu; Ketmanee Kliangklom; Jatuporn Thongsri (My University, 2022)
Several ultrasonic cleaning tanks (UCTs) had a problem: a manufacturer complained that there were damages to cleaning objects, they were unclarified, and it needed to be abruptly solved. To investigate and solve the problem, a small UCT filled with 3.92 L of water, with a frequency of 28 kHz, two horn transducers, and a total power of 100 W was built for simulation and experiment. A built tank body material of UCT can be adjustable to acrylic, glass, and stainless steel. Since the cavitation causing the cleaning relates to acoustic pressure, harmonic response analysis (HRA) in ANSYS software was employed to calculate the acoustic pressure inside the UCT for different designs such as mentioned materials, power, thickness, volume, and frequency. The HRA results revealed uneven acoustic pressure depending on the tank designs, consistent with foil corrosion and power concentration experiments. Furthermore, using the tank body material with acrylic, glass, and stainless steel provided the highest, moderate, and lowest acoustic pressure levels, respectively. The uneven acoustic pressure resulted from the differences in material transmission coefficients. In addition, the damage occurred because of improper tank design, resulting in excessive acoustic pressure. Therefore, the tank design is indispensable in designing high-efficiency UCTs to reduce damage and meet customer requirements.
Keywords: Ultrasound and Cavitation Phenomena